Drought and salinity tolerance of cool-season turfgrasses - Li, Jizhou, author; Qian, Yaling, advisor; Burcham, Daniel C., committee member; Ham, Jay, committee member; Zhang, Yao, committee member (Colorado State University. Libraries, 2024)
Due to the water scarcity and increased use of recycled water/saline water for turfgrass irrigation in arid and semi-arid climates, there is an increasing demand for drought and salt tolerant turfgrass. Kentucky bluegrass (Poa pratensis L.), tall fescue (Festuca arundinacea Schreb.), and perennial ryegrass (Lolium perenne L.) are the most commonly used cool season turfgrass species in the northern regions of the United States. The thesis includes two separate studies evaluating entries in National Turfgrass Evaluation Program (NTEP) trials. These two trials were conducted to identify the most drought tolerant lines of Kentucky bluegrass and tall fescue grown in a field study, and the most salt tolerant lines of perennial ryegrass grown in a greenhouse study, respectively. The drought tolerance trial is presented in Chapter 1. In it, the drought tolerance of thirty-five cool-season turfgrasses, including 15 Kentucky bluegrass lines, 19 tall fescue lines, and 1 perennial ryegrass line were evaluated under three deficit irrigation treatments, 40%, 60% and 80% evapotranspiration (ETo) from 2018 to 2020. Overall turfgrass quality, minimum irrigation requirement for maintaining the acceptable quality, and length of time to maintain acceptable quality were determined for each entry. The amount of irrigation needed to maintain acceptable quality for tall fescue was 71% - 95% ETo, and for Kentucky bluegrass, it was 81% - 110% ETo under three-year deficit irrigation. Based on turf quality and irrigation requirement to maintain acceptable quality during the three-year deficit irrigation period, we have identified the most drought tolerant entries. Among Kentucky bluegrass entries, "PST-K13-141" has emerged as the top performer, demonstrating an 81% ETo rate to maintain acceptable quality. Among tall fescue lines, the most drought-tolerant entries include "PST-5SDS," "Kingdom," "DLFPS 321/3679," and "Thor," requiring 71%, 74%, 74%, and 72% ETo, respectively, to uphold satisfactory turf quality. The results of this study suggest that selecting species and entries that use less water while maintaining acceptable quality could mitigate irrigation demands. In Chapter 2, the salt tolerance of eighty-three perennial ryegrass lines was evaluated in two separate greenhouse experiments. Eighty-three lines were grown in cone-shaped containers that were soaked in increasingly saline nutrient solution for 1 hour per day. The solution began with an electrical conductivity (EC) of 6.0 dS·m-1 and was subsequently increased by 4.0 dS·m-1 (in Experiment I) or 6.0 dS·m-1 (in Experiment II) every 3 weeks until reaching the next targeted salinity level. The final targeted salinity level was 22 dS·m-1. Grasses were grown under each of the 4 or 5 targeted salinity levels for a period of 3 weeks. Clipping yield reduction, overall turf quality, leaf firing, and density were determined at each salinity level. Regression analysis was conducted to determine the relationship between clipping yield and salinity. The salinity level causing a 25% reduction in clipping yield was used as an indicator of salinity tolerance level in different entries. We found that entries "SGP4", "PPG-PR 667", "PVF-SGS5", "BAR LP 22262", "GO-RUS21", "PPG-PR 610", "DLF-PR 3727", and "PPG-PR 639" were the most salt-tolerant, evidenced by the best turfgrass quality and the highest salinity levels at which there was a 25% clipping yield reduction in two experiments. We observed that the salinity levels that caused a 25% clipping yield reduction ranged from 5.0-8.8 dS·m-1 in experiment I and 5.7-10.7 dS·m-1 in experiment II. The entries with better salt tolerance identified in this study would hold the potential to be utilized on sites with marginally elevated saline soil. Additionally, they could be beneficial for locations where irrigation involves waters with elevated salinity, such as recycled water.
Keywords: drought stress; perennial ryegrass; tall fescue; Kentucky bluegrass; cool-season turf grass; salinity stress